Grounded Theory in Second/Foreign Language Education Research - Muhlisin Rasuki (ELLITE, 2021)
Grounded theory constitutes research methodology commonly used in the field of social sciences to investigate social phenomena. This research methodology, however, has rarely been used in the field of second/foreign language education. Given that second/foreign language education may be viewed as a social activity and that certain issues in second/foreign language education may be studied from social science perspectives, the present article surveys key literature on grounded theory. The goal is to help second/foreign language researchers assess the potential of this research methodology for studying relevant issues in the field of second/foreign language education.